Willingness to pay for one-stop anesthesia in pediatric day surgery - Di Caro Elisabetta; Bonomo Roberta; Bianco Franco; Mangia Giovanni; Frattarelli Eufrasia; Presutti Paola (BMC, 2011)
Abstract Background This study assesses the parents' Willingness To Pay (WTP) for One Stop Anesthesia (OSA). OSA is part of a free screening procedure that determines the timing of the anesthesiological assessment. In OSA-positive patients, the preoperative assessment is carried out on the same day as the surgery. The OSA allows patients who have to undergo surgery in a pediatric day surgery to avoid accessing the pre-admission clinic. Method This is a descriptive cohort study. A sample of 106 parents were interviewed directly by means of a questionnaire. The questionnaire builds a hypothetical scenario where the interviewee has a chance to buy the OSA health service with the WTP. The WTP values are distributed in classes and are contingent to the market built in the questionnaire. The Chi Square and Cramer's V tests evaluate the WTP dependence on the parents' place of origin and occupation. Results The approximate average of the WTP classes is €87.21 per family. The Chi Square test relative to the WTP classes and the places of origin is statistically significant (p < 0.05). The Cramer's V test is 0.347 and points to a positive association between the two demographics. The Cramer's V test of the WTP classes and the types of job is 0.339 and indicates a positive association. Conclusion Nearly 90% of pediatric patients who were screened for timing the preoperative assessment are true positives to OSA. This allows doing away with the pre-hospitalization, with definite advantages for the families. This screening is a health service that families would be hypothetically willing to pay.